Return on Equity Sebagai Antesenden Degree of Operating Leverage dan Degree of Financial Leverage: Studi Empiris pada Perusahaan Makanan dan Minuman - M. Rayhan Azis; Muhamad Umar Mai; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The aim of this research are to know the effect of Degree of Operating Leverage (DOL) and Degree of Financial Leverage (DFL) on Return on Equity (ROE) at Food and Beverage Companies Listed on Indonesia Stock Exchange (BEI) Period 2015-2019. This study uses secondary data in the form of complete annual financial statements for the 2015-2019 period, sourced from the Indonesia Stock Exchange. The research sample was 10 companies using purposive sampling technique or sampling with several considerations. The types of data used in this study are time series and cross sections. The research method used is associative research with a quantitative approach. The analysis used to determine the effect of DOL and DFL on ROE is multiple linear regression analysis with Random Effect Model approach using Eviews 9 software. DOL, and DFL simultaneously have a significant effect on ROE. DOL, and DFL partially have a negative and significant effect on ROE.